Mechanical thrombectomy for acute ischemic stroke: final results of the Multi MERCI trial - Smith, Wade S; Sung, Gene; Saver, Jeffrey; Budzik, Ronald; Duckwiler, Gary; Liebeskind, David S; Lutsep, Helmi L; Rymer, Marilyn M; Higashida, Randall T; Starkman, Sidney; Gobin, Y Pierre; Frei, Donald; et al. (Stroke (1970), 2008)
Endovascular mechanical thrombectomy may be used during acute ischemic stroke due to large vessel intracranial occlusion. First-generation MERCI devices achieved recanalization rates of 48% and, when coupled with intraarterial thrombolytic drugs, recanalization rates of 60% have been reported. Enhancements in embolectomy device design may improve recanalization rates. Multi MERCI was an international, multicenter, prospective, single-arm trial of thrombectomy in patients with large vessel stroke treated within 8 hours of symptom onset. Patients with persistent large vessel occlusion after IV tissue plasminogen activator treatment were included. Once the newer generation (L5 Retriever) device became available, investigators were instructed to use the L5 Retriever to open vessels and could subsequently use older generation devices and/or intraarterial tissue plasminogen activator. Primary outcome was recanalization of the target vessel. One hundred sixty-four patients received thrombectomy and 131 were initially treated with the L5 Retriever. Mean age+/-SD was 68+/-16 years, and baseline median (interquartile range) National Institutes of Health Stroke Scale score was 19 (15 to 23). Treatment with the L5 Retriever resulted in successful recanalization in 75 of 131 (57.3%) treatable vessels and in 91 of 131 (69.5%) after adjunctive therapy (intraarterial tissue plasminogen activator, mechanical). Overall, favorable clinical outcomes (modified Rankin Scale 0 to 2) occurred in 36% and mortality was 34%; both outcomes were significantly related to vascular recanalization. Symptomatic intracerebral hemorrhage occurred in 16 patients (9.8%); 4 (2.4%) of these were parenchymal hematoma type II. Clinically significant procedural complications occurred in 9 (5.5%) patients. Higher rates of recanalization were associated with a newer generation thrombectomy device compared with first-generation devices, but these differences did not achieve statistical significance. Mortality trended lower and the proportion of good clinical outcomes trended higher, consistent with better recanalization.